ChemInform Abstract: Three New Lycopodium Alkaloids from Phlegmariurus fargesii. Issue 33 (July 2016) - Hao, Li‐Jun; Zhou, Yun‐Jing; Wang, Lu‐Lu; Pan, Ke
Abstract: Three new Lycopodium alkaloids fargesiine A (Ia), fargesiine B (Ib), and fargesiine C (II) are isolated from Phlegmariurus fargesii together with one known compound.